(untitled) (International Journal of Information and Electronics Engineering, 2023)
This study highlights how artificial intelligence, or AI, can be applied to cybersecurity using dynamic honeypots and auto-generating fake data trails. This seeks to decrease threat detection, misdirection of attackers, and collection